LIQUIDITY AND PROFITABILITY ON FIRM VALUE IN LQ45 COMPANIES - Laynita Sari; Anaya Ismawati Putri; Dewi Zulvia; Mike Kusuma Dewi (Yayasan Education and Social Center, 2026)
This study aims to analyze the effect of liquidity and profitability on firm value in LQ45 companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Liquidity is measured using the Current Ratio (CR), profitability is measured by Return on Assets (ROA), while firm value is proxied by Price to Book Value (PBV). The study applies a quantitative research approach using panel data analysis to evaluate the relationship between the independent and dependent variables. The sample consists of 27 companies included in the LQ45 index, with a total of 108 observations selected through purposive sampling techniques based on predetermined criteria. The findings reveal that liquidity has a positive and significant effect on firm value, indicating that companies with stronger liquidity positions tend to have higher market valuations. Meanwhile, profitability shows a positive but insignificant effect on firm value, suggesting that increases in profitability do not necessarily lead to significant changes in market perception or company valuation during the observed period